Molecular detection and assemblage analysis of the intestinal protozoan Giardia duodenalis in wild boars in Korea - Haeseung Lee; Dongmi Kwak (Frontiers in Veterinary Science, 2023)
Giardia duodenalis (syn. G. intestinalis, G. lamblia) is the only Giardia species that infects humans and most other mammals. Wild boars are a reservoir of many viruses, bacteria, and parasites that can be transmitted to livestock and humans. This study examined the infection rate of G. duodenalis in wild boars and confirmed its specificity by comparing assemblages through PCR amplification of the 18S rRNA, gdh, and β-giardin genes. Fecal samples were collected from roadkilled or trapped wild boars from April 2016 to December 2021 in Korea. DNA was extracted directly from 612 wild boar fecal specimens using a commercial kit. PCR was performed targeting the 18S rRNA region, β-giardin, and glutamate dehydrogenase genes of G. duodenalis. Some PCR-positive samples were selected for sequencing analysis. The obtained sequences were subsequently used for phylogenetic tree construction. Of the 612 samples tested, 125 (20.4%) were positive for G. duodenalis. The highest infection rate was detected in the central region (12.0%) and in autumn (12.7%). Among the risk factors, the seasonal factor was statistically significant (p = 0.012). Phylogenetic analysis revealed three genetic assemblages: A, B, and E. Assemblages A and B exhibited 100% identity with Giardia sequences isolated from human and farmed pigs in Korea and Japan. This result cannot be ignored because it indicates the possibility of zoonotic transmission. Therefore, continuous management and monitoring of this pathogen are necessary to prevent transmission and protect animal and human health.